2021
DOI: 10.1088/1755-1315/733/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

The potential of rice husk ash for silica synthesis as a semiconductor material for monocrystalline solar cell: a review

Abstract: The solar cell is a device that can convert solar energy into electrical energy. The solar cell is promising energy because it is environmentally friendly compared to fossil fuel. The essential component in the solar cells is silicon. Silicon is a semiconductor that can absorb sunlight. However, the available solar cells currently have relatively high prices since the semiconductor compiler material requires many processes and expensive. Rice husk ash can be used as a producer of environmentally friendly silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The maximum documented silica gel production for other feedstocks, including palm shell, was lower than the present precursor with the best silica gel yield 92% [54], corn cob 47% [19], bamboo Leaf 79.38% [49], sugarcane leaf 80.50% [55], wheat straw (7.00% [21], and rice straw 76.70% [56]. The highest yield from the TS was, however, only slightly higher than that of sugarcane bagasse and rice husk, both of which have yields greater than 95% [57] and 96% [13,46], respectively. This demonstrates that one of the potential precursors for producing silica gel can be the TS.…”
Section: Yield Of Silica Gelcontrasting
confidence: 54%
See 2 more Smart Citations
“…The maximum documented silica gel production for other feedstocks, including palm shell, was lower than the present precursor with the best silica gel yield 92% [54], corn cob 47% [19], bamboo Leaf 79.38% [49], sugarcane leaf 80.50% [55], wheat straw (7.00% [21], and rice straw 76.70% [56]. The highest yield from the TS was, however, only slightly higher than that of sugarcane bagasse and rice husk, both of which have yields greater than 95% [57] and 96% [13,46], respectively. This demonstrates that one of the potential precursors for producing silica gel can be the TS.…”
Section: Yield Of Silica Gelcontrasting
confidence: 54%
“…Therefore, it is an essential to look for a feasible and affordable method to produce silica gel. In this line, as a substitute in this case, preparation of silica gel using leftover biomass, such as rice husk ash [13], sugarcane leaf [14], palm tree [15], rice straw [16], oat husk [17], sugarcane bagasse [14], coffee husk [18], corn cob [19,20], wheat straw [21], maize leaves [22], bamboo leaf [23], and teff straw [24] are gaining more interest because of this approach addresses simple manufacturing procedure and economically affordable , can be a better option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te bandgap energy is the primary factor that determines how a semiconductor interacts with other materials. Te difference between the valence band and the conduction band section, which defnes the amount of transition energy required to convert the electron band from the valence band to the conduction band, is determined by the energy bandgap [182]. Bandgap energy for semiconductors ranges from 0 to 4 eV, whereas it is beyond 4 eV for isolators and below 0.5 eV for conductors [183].…”
Section: Applications In Watermentioning
confidence: 99%
“…In general, silicon oxide in the ash of rice husks is 94-96%. Those who performed activities such as preparing the ashes of the rice husk, washing, obtaining Silicon by enrichment, and checking permeability [6]. The possibilities of obtaining technical silicon were studied on the basis of experiments carried out by returning it with carbon in an electric arc furnace, and it was found that it is possible to obtain technical Silicon of the brand Kr0, Kr1 [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%